Pre-Disaster Management of Tropical Cyclone Seroja to Realize Disaster Resilient Area in Rote Ndao Regency, East Nusa Tenggara Province - Haryadi Haryadi; Pujo Widodo; Sobar Sutisna; Ali Rahmat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The author focuses on the problem of tropical cyclone Seroja which is known to have hit Rote Ndao Regency for the first time and how to deal with it if the disaster occurs again, so good management is needed. The purpose of this research is to find out how BPBD manages activities in dealing with the Seroja tropical cyclone disaster if it occurs again. This research uses qualitative methods with data collection techniques used through observation, interviews and documentation. In accordance with the type of research above, the authors used an interactive model from Miles, Huberman and Saldana (2019) to analyze the research data with 3 steps, namely data reduction, data presentation and conclusion drawing/verification.The findings obtained by the author in this study are that the management by BPBD in the Seroja tropical cyclone disaster is quite good, however, it still has constraints on funding and manpower which are still lacking. Disaster management in dealing with the Seroja tropical cyclone in Rote Ndao Regency is classified as good, this is because there is good coordination between BPBD and related regional apparatus in overcoming disasters in pre-disaster activities. in order to improve disaster resilient areas, it is advisable to optimize the use of local communities to be ready and alert in the face of disasters.